The Role of Aristotelian Appeals in Influencing Consumer Behavior - Lamichhane, Yog Raj (Journal of Development and Social Engineering, 2017)
The purpose of this paper is to identify the effects of some representative print advertisements on consumer, relating to Aristotelian appeals- ethos, logos and pathos individually or simultaneously. How advertisers utilized this trinity to influence the behavior of consumers to use their products and services is the major concern of this study. For this, nine print advertisements which were published in two English newspapers of Nepal are studied. These adverts are conveniently taken from the Republica and The Himalayan Times of 15 and 16 February 2017. It accomplishes the intense assessment and yawning interpretation of the entire selected samples to expose the newspaper advertising behavior using content analysis. Languages of advertising are read between the lines. Used images and colors are also discussed relating to their symbolic meanings. Marketing strategies like free offer, buy one get one free, discounts, celebrity endorsement, expert opinion, sex appeals, etc are highly exercised to craft credibility, sentiment and reason to move audience and seeming common concepts and objects are transferred into highly desirable services and products. Maximum advertisers are so mindful to merge language, image and color according to their nature of product and service keeping literate audience in mind. So, the study notifies the consumers about how they are being influenced by Aristotelian appeals and equips advertisers with tool and process of influencing consumer behavior while making advertisement. Among this trinity of ethos, pathos and logos, emotion is observed almost unavoidable and the emotion is also contributive to make ethos and logos more effective. Nevertheless it seems as black sheep, but the appropriate amalgamation of ethos, pathos and logos appears successful.